2018 IEEE Conference on Standards for Communications and Networking (CSCN) 2018
DOI: 10.1109/cscn.2018.8581855
|View full text |Cite
|
Sign up to set email alerts
|

Service Provisioning in Vehicular Networks Through Edge and Cloud: An Empirical Analysis

Abstract: This is the accepted version of the original article published by IEEE.Abstract-Vehicular Cloud Computing is a network infrastructure paradigm that has been largely used in the vehicular systems landscape for improving drivers' experience. In particular, the higher computational resources made available by cloud computing technologies have helped in coping with the tremendous growth of data traffic exchanged within vehicular networks. However, the advanced development of such infrastructure, together with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…For instance, vehicles are typically not affected by strict memory, processing, storage, and energy limitations, which enables the integration of various sensors, wireless transmitters and processing components. In recent years, several advanced technologies such as lightweight virtualization and edge computing have been applied to smart vehicles to enable novel applications and dynamic service deployment [25], [31], [32].…”
Section: B Requirements and Performance Metricsmentioning
confidence: 99%
“…For instance, vehicles are typically not affected by strict memory, processing, storage, and energy limitations, which enables the integration of various sensors, wireless transmitters and processing components. In recent years, several advanced technologies such as lightweight virtualization and edge computing have been applied to smart vehicles to enable novel applications and dynamic service deployment [25], [31], [32].…”
Section: B Requirements and Performance Metricsmentioning
confidence: 99%
“…There are a number of studies that have examined the performance and scalability of communication protocols. Some studies have found that the throughput in MQTT drops significantly as the number of clients' subscriptions increases [112], [113]. In [114], the authors compared the performance of DDS and MQTT.…”
Section: Scalability and Performancementioning
confidence: 99%
“…Nevertheless, offloading schemes [33], where all vehicles offload their tasks to the same VEC server, can limit the performance gain due to overload. Multi-Access Edge Computing (MEC) [34] is an emerging network paradigm that can be exploited also in vehicular scenarios to foster a more effective and flexible service delivery. Therefore, we combine edge computing and Q-learning into the platoon.…”
Section: B Platooning Edge Computingmentioning
confidence: 99%